2008
DOI: 10.1182/blood.v112.11.4255.4255
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Use of Imatinib Plasma Levels in Patients with Chronic Myeloid Leukemia (CML)

Abstract: Background: Imatinib plasma levels have been reported to correlate with response to therapy and possibly toxicity (Larson et al, Blood 2008; Picard et al, Blood 2007). These studies included patients taking standard dose, once daily imatinib. However, patients are frequently receiving imatinib at different doses and schedules that do not permit extrapolation of these results. Aims: To investigate the significance of plasma levels in patients receiving imatinib at various doses and schedules. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…86 However, other investigators have suggested that plasma levels of imatinib in patients receiving different dose schedules had no correlation with response to therapy. 88,89 The clinical value of monitoring plasma levels of imatinib remains to be defined. Monitoring imatinib plasma levels may be useful in determining patient adherence to therapy.…”
Section: Primary Treatmentmentioning
confidence: 99%
“…86 However, other investigators have suggested that plasma levels of imatinib in patients receiving different dose schedules had no correlation with response to therapy. 88,89 The clinical value of monitoring plasma levels of imatinib remains to be defined. Monitoring imatinib plasma levels may be useful in determining patient adherence to therapy.…”
Section: Primary Treatmentmentioning
confidence: 99%